A COMPARATIVE STUDY ON THE USE OF ARTICLES IN ENGLISH AND GERMAN - Kumbino Kumbino (FEB UNTAG Semarang, 2013)
Article is one of the important things when someone studies a language. In general, articles both in English and German have the same meaning, but different forms and functions will be seen in the sentences. These differences are supposed to be understood. In English, the definite and indefinite articles do not change at all in the gender and the plural forms of the words which follow, as well as in nominative case (as subject), accusative case (as direct object), dative case (as indirect object), and genitive case (as possession). On the other hand, in German, the articles change in the cases mentioned above. After analyzing the articles of both languages, the writer concludes that there are similarities and differences as well in using articles in English and German. The similarities are when we use the articles before the only one subject, for mentioning the second time, before names of group of islands and before superlative adjectives. Meanwhile, in German when we use articles for genders, singular and plural nouns, and cases, it will differ extremely from English.